Frágil culpabilidad. El conflicto entre arrogancia moral y sabiduría trágica en Eurípides. (2012)
In Euripides the thesis of the human character of fault and punishment is found; turning the responsibility into an immanent subject to men s life in spite of the religious beliefs. In this sense the law; the human passions; rationality and faith get into a tension that has been continuing; taking place regardless of the moral renewal of modernity. This article will be structured following some fundamental moral themes of several of the aforementioned thinker s tragedies from a mainly genealogical and hermeneutical perspective; making an intra- and inter-textual analysis that allows to put into consideration the importance of the tragic wisdom for the instruction of a moral fallible and historic conscience.